Building Student Character through Al-Islam and Kemuhammadiyahan Education: A Systematic Literature Review - Mar’atus Sholihah; Junaidi (MultiTech Publisher, 2024)
Al-Islam and Kemuhammadiyahan (AIK) education plays an important role in shaping student character in Muhammadiyah Universities (PTM). This research uses the Systematic Literature Review (SLR) method with data from Google Scholar to examine the role of AIK. The search process was conducted in four stages: (1) the keyword “Character Education” produced 194,000 documents (2019-2023), (2) adding “Al-Islam” produced 6,260 documents, (3) adding “Kemuhammadiyahan” produced 1,120 documents, and (4) adding “Student” produced 531 documents. Filtering based on inclusion resulted in 10 articles being analyzed. The results show that AIK is effective in building moral values, nationalism, and student leadership. This study is relevant for the development of character education policies in PTM and other institutions that apply similar approaches